Strain-resolved analysis of hospital rooms and infants reveals overlap between the human and room microbiome - Brandon Brooks; Matthew R. Olm; Brian A. Firek; Robyn Baker; Brian C. Thomas; Michael J. Morowitz; Jillian F. Banfield (Nature Communications, 2017)
It is thought that the hospital environment may contribute to infant microbiome development. Here, Brooks et al. present a genome-resolved metagenomic study of microbial genotypes from the infant gut and from neonatal intensive care unit rooms, showing that some strains are found in both infants and rooms.